Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 123859 by sdfg last updated on 28/Nov/20

∫sect e^t  dt

sectetdt

Answered by mindispower last updated on 29/Nov/20

sec(x)=(2/(e^(ix) +e^(−ix) )),we use cos(x)=((e^(ix) +e^(−ix) )/2)  =((2e^(ix) )/(1+e^(2ix) ))=2Σ_(n≥0) (−1)^n e^((2n+1)ix)   ∫sec(x)e^x dx=2∫Σ_(n≥0) (−1)^n e^((2n+1)ix+x) dx  2Σ_(n≥0) (−1)^n ∫e^((2n+1)ix+x) dx  =2Σ_(n≥0) (−1)^n (e^(((2n+1)i+1)x) /((2n+1)i+1))+c  =2e^((1+i)x) Σ_(n≥0) (((−e^(2ix) )^n )/((2n+1)i+1))  =2e^((1+i)x) Σ_(n≥0) ((−i(−e^(2ix) )^n )/(2n+1−i))=e^((1+i)x) Σ_(n≥0) (((−i)(−e^(2ix) )^n )/(n+(((1−i)/2))))  =e^((1+i)x) Σ_(n≥0) (((−i)(−e^(2ix) )^n )/(n!)).((n!)/(n+(((1−i)/2))))  =e^((1+i)x) (((−2i)/(1−i))+Σ_(n≥1) (((−i)(−e^(2ix) )^n .Π_(k=0) ^(n−1) (k+(((1−i)/2)).Π_(k=0) ^(n−1) (1+k))/(Π_(k=0) ^(n−1) (k+(((3−i)/2))).(((1−i)/2))))  =−((2i)/(1−i))e^((1+i)x) (1+((1−i)/(−2i))Σ_(n≥1) (((−i))/((((1−i)/2)))).(((((1−i)/2))_n (1)_n )/((((3−i)/2))_n )).(((−e^(2ix) )^n )/(n!)))  =(1−i)e^((1+i)x) (1+Σ_(n≥1) (((((1−i)/2))_n (1)_n )/((((3−i)/2))_n )).(((−e^(2ix) )^n )/(n!)))+c  (a)_n =Π_(k=0) ^(n−1) (a+k),n!=1......n=(1+0)....(1+(n−1))  =(1)_n ....we used this all  long  now use 2F_1 (a,b;c;[x])=(1+Σ_(n≥1) (((a_n )(b)_n )/((c)_n )).(x^n /(n!)))  we get  =(1−i)e_  ^((1+i)x)   _2 F_1 (((1−i)/2),1;((3−i)/2),[−e^(2ix) ])+C  C constante  ∫sec(x)e^x dx=(1−i)e^((1+i)x)   _2 F_1 (((1−i)/2),1,((3−i)/2);[−e^(2ix) ])+C  [X] is argument of function not floor function

sec(x)=2eix+eix,weusecos(x)=eix+eix2=2eix1+e2ix=2n0(1)ne(2n+1)ixsec(x)exdx=2n0(1)ne(2n+1)ix+xdx2n0(1)ne(2n+1)ix+xdx=2n0(1)ne((2n+1)i+1)x(2n+1)i+1+c=2e(1+i)xn0(e2ix)n(2n+1)i+1=2e(1+i)xn0i(e2ix)n2n+1i=e(1+i)xn0(i)(e2ix)nn+(1i2)=e(1+i)xn0(i)(e2ix)nn!.n!n+(1i2)=e(1+i)x(2i1i+n1(i)(e2ix)n.n1k=0(k+(1i2).n1k=0(1+k)n1k=0(k+(3i2)).(1i2)=2i1ie(1+i)x(1+1i2in1(i)(1i2).(1i2)n(1)n(3i2)n.(e2ix)nn!)=(1i)e(1+i)x(1+n1(1i2)n(1)n(3i2)n.(e2ix)nn!)+c(a)n=n1k=0(a+k),n!=1......n=(1+0)....(1+(n1))=(1)n....weusedthisalllongnowuse2F1(a,b;c;[x])=(1+n1(an)(b)n(c)n.xnn!)weget=(1i)e(1+i)x2F1(1i2,1;3i2,[e2ix])+CCconstantesec(x)exdx=(1i)e(1+i)x2F1(1i2,1,3i2;[e2ix])+C[X]isargumentoffunctionnotfloorfunction

Terms of Service

Privacy Policy

Contact: info@tinkutara.com